A comparative study of nature of adnexal masses by ultrasonography and histopathology - Roshed, Md Mahabubur; Akhter, Mst Dalia; Hossain, Syed Mozammel (Bangladesh Medical Journal Khulna, 2019)
Background: Adnexal masses are common lesions in women across the globe. This is also important for woman in Bangladesh. The incidence of adnexal malignancy ranks only after the carcinoma of cervix and endometrium. So their accurate and early diagnosis is necessary for design management and treatment protocol. Objective: The aim of the study is to assess the correlation between histopathological examination and ultrasonographic evaluation in making early and confirm diagnosis of adnexal masses. Methodology: Eighty four women with different ages having adnexal mass, diagnosed by ultrasonographic evaluations and followed by surgery were included in this study between january 12 to December, 14. The morphologic characteristics of the masses were evaluated with gray scale Ultrasonography (USG). Specimens were collected after surgical resection in a container containing 10% formalin. The specimens were processed by paraffin embedding method and stained by routine Haematoxylin and Eosin stain for microscopic examination. The results of this study were calculated by standard statistical formula. Results: Histopathological examination revealed that 68 masses (80.95%) were benign, two (2.38%) were borderline malignant, and 16 (19.05%) were malignant. USG enabled correct diagnosis of 63 of the 68 benign masses (92.65%) and all 16 malignant masses (100%). Conclusion: There is a correlation between histopathological examination and ultrasonographic evaluation of adnexal masses in most cases. Therefore the imaging analysis of internal architectural appearance by USG and histopathological examination increases the specificity in the diagnosis of adnexal masses. Bang Med J (Khulna) 2018; 51 : 7-11